The age of Netflix : critical essays on streaming media, digital delivery and instant access - Barker, Cory, 1988-; Wiatrowski, Myc (McFarland & Company, Inc., Publishers, 2017)
"In 2016, Netflix expanded its online streaming video service to 130 new countries, adding more than 12 million subscribers in nine months and bringing its total to 87 million. In this collection of new essays, contributors explore how Netflix has become a cultural institution and transformed the way we consume popular media"-- Provided by publisher
Keywords: Netflix (Firm); Streaming video -- Social aspects.; Streaming technology (Telecommunications) -- Social aspects.; Mass media -- Social aspects.; Vidéo en continu -- Aspect social.; En continu (Télécommunications) -- Aspect social.; Médias -- Aspect social.; BUSINESS & ECONOMICS -- Industries -- Media & Communications.; TECHNOLOGY & ENGINEERING -- Telecommunications.; Mass media -- Social aspects